Addressing challenges to human health in the Anthropocene epoch—an overview of the findings of the Rockefeller/Lancet Commission on Planetary Health. Issue 1 (December 2016) - Haines, Andy
Abstract The report of the Rockefeller Foundation/Lancet Commission on Planetary Health described how human health directly depends upon the environment. It takes a broad perspective not only acknowledging climate change as the most important global environmental threat to health but also recognizing other impacts, including dramatic loss of tropical forests, land degradation, loss of biodiversity, declining freshwater resources, ocean acidification, and over-exploitation of fisheries. All pose challenges to human health gains, leading to the concept of planetary health—that the human condition is tied to natural systems. The Planetary Health Commission report highlights several major concerns arising from environmental change including impacts on food availability and quality, increases in natural disasters and population displacement, and newly emerging diseases, e.g. from zoonotic infections. Three challenges emerge from the report: the first is imagination, or conceptual challenges—better metrics are needed to assess human progress within the context of environmental change; the second is a lack of relevant knowledge, requiring more research on the inter-linkages between environmental change and health and on the effectiveness of potential solutions; and the third is implementation of solutions, ensuring that the science is translated into policy and practice. There are many opportunities to promote planetary health including developing sustainable and healthy cities, encouraging more resilient health systems and disaster preparedness, reducing food waste, preserving ecosystems, and redirecting harmful subsidies in food, agriculture, fishery and energy sectors. Many current trends are driven by inequitable, inefficient, and unsustainable patterns of resource consumption and technological development, coupled with population growth, but solutions lie within reach. Prosperity must be redefined as an enhancement of the quality of life and the delivery of improved health for all, together with respect for natural systems.